Teknologi Informasi: Dampak Media Sosial pada Perubahan Sosial Masyarakat - Fauziah, Isna Nadifah Nur; Saputri, Selly Ade; Herlambang, Yusuf Tri (Indo-MathEdu Intellectuals Journal, 2024)
The development of information technology brings a change in society. The birth of social media caused people's behavior patterns to experience a shift in existing culture, ethics, and norms. Indonesia, with its large population and diverse ethnic, racial, and religious cultures, has a lot of potential for social change. This article aims to analyze the consequences caused by social media and aims to ensure that social media can be used more wisely by using literature methods in the form of a literature review. The data analysis technique in this article is to collect library data from national and international journals that are relevant to information technology. The results and conclusions in this writing are that the existence of social media has influenced social life in society. Changes in social relationships or as changes to the balance (equilibrium) of social relationships and all forms of changes in social institutions in a society, which affect the social system, including values, attitudes, and behavioral patterns between groups in society. Positive social changes such as ease of obtaining and conveying information, obtaining social and economic benefits. Meanwhile, social changes tend to be negative, such as the emergence of social groups in the name of religion, ethnicity and certain behavioral patterns which sometimes deviate from existing norms